Mekanisme Penyelesaian Kejahatan Insider Trading dan Solusi dalam Mewujudkan Perlindungan Hukum Bagi Investor Pasar Modal - Eka Prawira Rajaras Ps (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Internal trafficking or insider trading is a form of prohibited securities transactions in the capital market, because it violates the principle of transparency which is the main basis for capital market activity.  The background of this study is the rise of insider trading practices in securities trading activities.  The main purpose of this study is to analyze how the completion system of the practice of insider trading is running and how legal protection can be given to investors who are victims.  This study uses a normative juridical approach by comparing applicable regulations.  The results of the study show that investors who suffer losses due to insider trading can file a lawsuit against the law as a legal step to obtain legal protection